#Free_CeCe: the material convergence of social media activism. Issue 5 (2nd September 2016) - Fischer, Mia
Abstract: In 2011 CeCe McDonald, an African-American transgender woman, was charged with murder for killing her attacker during a racist and transphobic assault in Minneapolis. After McDonald's arrest, local queer communities organized an astounding level of support. This article examines the CeCe Support Committee as a case study for effective grassroots organizing that is fueled by and increasingly reliant upon social media for advancing social justice. An ethnographic approach reveals how the success of the Committee's social media activism largely depended on traditional activist strategies. Because the group's activism was based on unpaid labor and supported by numerous physical protests, the use of social media platforms enabled the Support Committee to challenge news media's racialized framing of McDonald's gender non-conformity as deceiving and threatening and exposed the state-sanctioned violence enacted against her. Therefore, I contend that the transformative political potential of social media activism is only possible when sustained by coordinated, "on-the-ground" activism offline. Moreover, this case study illustrates that intersecting oppressions do not simply disappear in online activism, but that those oppressions—particularly the centrality of whiteness in organizing—continue to constrain the actual material achievements of social media activism. For the CeCe Support Committee the convergence of on- and offline activism resulted in a raised public consciousness about the disposability of transgender lives, turning a national spotlight on the violence transgender people face.